2011
DOI: 10.1210/jc.2010-2140
|View full text |Cite
|
Sign up to set email alerts
|

Serum Pigment Epithelium-Derived Factor Is Elevated in Women with Polycystic Ovary Syndrome and Correlates with Insulin Resistance

Abstract: The serum PEDF level is elevated in women with PCOS and is associated with IR. PEDF may play a role in the pathogenesis of IR in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 26 publications
5
37
1
Order By: Relevance
“…Data from our group on circulating PEDF levels reported no difference between obese women with PCOS and age-and BMI-matched controls (Lecke et al 2013a), in accordance with a previous study with obese PCOS patients (Joham et al 2012). In normal-weight PCOS Chinese women, higher PEDF values were associated with insulin resistance (Yang et al 2011) and ultra-sensitive CRP (Cheng et al 2013). Recently, we have reported that PEDF mRNA in SC adipose tissue of PCOS women was similar to that found in age-and BMI-matched controls.…”
Section: Visfatinsupporting
confidence: 90%
“…Data from our group on circulating PEDF levels reported no difference between obese women with PCOS and age-and BMI-matched controls (Lecke et al 2013a), in accordance with a previous study with obese PCOS patients (Joham et al 2012). In normal-weight PCOS Chinese women, higher PEDF values were associated with insulin resistance (Yang et al 2011) and ultra-sensitive CRP (Cheng et al 2013). Recently, we have reported that PEDF mRNA in SC adipose tissue of PCOS women was similar to that found in age-and BMI-matched controls.…”
Section: Visfatinsupporting
confidence: 90%
“…Insulin resistance is associated with elevated plasma PEDF in humans (32,38), and PEDF causes glucose intolerance and insulin resistance in cultured cells and mice (5,13,20). Fasting blood glucose and insulin were similar in WT and PEDF-aP2 mice (Table 2), and adipose-specific PEDF overexpression did not significantly affect glucose tolerance (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Much less is known regarding the antiangiogenic factors secreted locally and the role they play in the regulation of angiogenesis in expanding adipose tissue. PEDF is a major endogenous inhibitor of angiogenesis, circulating levels of PEDF are tightly correlated with obesity (25,26,30,32,37,38), and adipocytes are a major source of PEDF (13,20). Studies of human primary adipocytes have demonstrated that PEDF secretion is eightfold greater than adiponectin secretion and 140-fold greater than VEGF secretion (20).…”
Section: Discussionmentioning
confidence: 99%
“…It was performed 6-8 day after oral glucose tolerance test as described previously [18][19][20]: after fasting overnight, subjects were admitted to the hospital, where iv cannulas were placed in both arms for insulin and glucose infusion and for blood sampling. A priming dose of insulin was given followed by an infusion (120mIU/ m 2 /min) of short-acting human insulin (Lilly, Humulin, USA) for 120 min.…”
Section: Hyperinsulinemic-euglycemic Clampmentioning
confidence: 99%